2002
DOI: 10.1161/01.hyp.0000036452.28493.74
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of AT 1A Receptor in the Development of 2K1C Hypertension

Abstract: Abstract-The aims of this study were to delineate the relative contribution of angiotensin II (ANG II) subtype 1A (AT 1A ) and 1B (AT 1B ) receptors to the development of two-kidney, one-clip (2K1C) Goldblatt hypertension in mice, to examine if increased nitric oxide synthase (NOS) activity counteracts the vasoconstrictor influences of ANG II in 2K1C hypertensive mice, and to determine the role of ANG II type 2 (AT 2 ) receptors in 2K1C hypertension in mice. AT 1A ANG II receptor knockout (AT 1A Ϫ/Ϫ) and wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 47 publications
10
71
1
1
Order By: Relevance
“…It is also possible that high doses of ANG II facilitate interactions with other receptors, like AT 2 R and megalin, that may counteract AT 1 R actions. However, in the case of the AT 2 R, findings by Cervenka et al (4) and Wesseling et al (37) point out that it is unlikely that AT 2 R activation contributes significantly to the ANG II-mediated increases in arterial pressure during ANG II-dependent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that high doses of ANG II facilitate interactions with other receptors, like AT 2 R and megalin, that may counteract AT 1 R actions. However, in the case of the AT 2 R, findings by Cervenka et al (4) and Wesseling et al (37) point out that it is unlikely that AT 2 R activation contributes significantly to the ANG II-mediated increases in arterial pressure during ANG II-dependent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These responses may be interpreted by two different cellular mechanisms. First, total deletion of AT 1a receptors would lead to loss of all known responses to extracellular ANG II that are attributable to cell surface AT 1 receptors (6,7,14,17). This mechanism likely plays a predominant role in Agtr1aϪ/Ϫ mice (7,14).…”
Section: Discussionmentioning
confidence: 99%
“…Although PRA decreases soon after the development of renal artery stenosis, 4 Ang II still represents a primary stimulus via activation of Ang II type 1 receptor for the release of a number of bioactive compounds, including aldosterone, endothelin, and eicosanoids, 30 dently contribute to vasoconstriction, salt and water retention, vascular remodeling, renal fibrosis, and the decline in glomular filtration rate that ultimately determines the progression of the disease. 4 Furthermore, studies on 2-kidney, 1-clip renovascular hypertension in rats have shown that blocking the renin-angiotensin system prevented hypertension indefinitely.…”
Section: Discussionmentioning
confidence: 99%